Dietary forage to concentrate ratios impact on yak ruminal microbiota and metabolites - Pang, Kaiyue; Chai, Shatuo; Yang, Yingkui; Wang, Xun; Liu, Shujie; Wang, ShuXiang (Frontiers in Microbiology, 2022)
To improve the rumen fermentation function and growth performance of yaks (Bos grunniens), better understanding of the effect of different dietary forage to concentrate ratios on rumen microbiota and metabolites is needed. In the present study, three diets with different dietary forage to concentrate ratios (50:50, 65:35, and 80:20) were fed to 36 housed male yaks. The changes in the distribution of rumen microorganisms and metabolites and the interactions between them were studied by 16s rRNA gene sequencing and liquid chromatography-mass spectrometry (LC-MS). The diversity and richness of microorganisms in the rumen varied according to diet. The most abundant gate levels were Firmicutes and Bacteroidetes. Firmicutes was the most abundant in the C50 group but not significantly different from the other groups (p > 0.05), and the relative abundance of Bacteroidetes was significantly lower in the C65 group than in the C80 group (p < 0.05). The Christensenellaceae_R-7_group, Rikenellaceae_RC9_gut_group, and Methanobrevibacter had the highest relative abundances at the genus level. Among them, Christensenellace_R-7_group had the highest relative abundance in the C50 group, but it was not significant among the three groups. The Rikenellaceae_RC9_gut_group was significantly abundant in the C80 group compared with the C50 group. The Methanobrevibacter content was higher in the C65 group than in the other two groups, but not significantly. Both the concentration and metabolic pathways of rumen metabolites were influenced by the dietary concentrate ratio; lipids, lipid-like molecules, organic acid metabolites, and organic oxide-related metabolites differed between the groups. Significant changes were found for six metabolic pathways, including arginine and proline metabolism; glycine, serine, and threonine metabolism; glyoxylate and dicarboxylate metabolism; arginine biosynthesis; glycerophospholipid metabolism; glycerolipid metabolism; and nitrogen metabolism